Multicentre experience with the transcatheter valve repair system for tricuspid regurgitation. (14th October 2021) - Wild, M; Loew, K; Boekstegers, P; Markovic, S; Rosch, S; Lurz, P; Hausleiter, J
Abstract: Background: Tricuspid regurgitation (TR) is associated with high morbidity and mortality, but many patients are ineligible for surgical treatment due to age and co-morbidities. As a consequence, transcatheter treatment techniques have evolved over the last years. Leaflet repair is one of the most commonly used techniques and has recently gained commercial approval for dedicated TR treatment. The device offers the possibility for independent leaflet grasping and a central spacer can bridge larger coaptation gaps. The hitherto evidence is mainly based on compassionate use data. This is the first report on commercial use in a multicenter study with a large patient cohort and long-term follow-up. Purpose: To investigate safety and efficacy of the leaflet repair system in the treatment of TR in a commercial use setting. Methods: We retrospectively collected clinical and imaging data from all consecutive patients undergoing leaflet repair for TR at four tertiary care centres. A core laboratory analysis of the echocardiographic data has been performed. Baseline, procedural and follow-up data has been included in the analysis. Results: A total of 155 patients, treated between February 2019 and February 2021 has been included (mean age 77±8 years, 52% female). Mean STS score was 7.7±6.7%. TR was of functional etiology in the majority (82%) of patients and was severe or higher graded in 87% (mean EROA 68±47 mm 2 ). Patients were highly symptomatic with exertional dyspnea NYHA functional class III/IV in 91%. Technical success was achieved in 97% and TR was successfully reduced to ≤2+ in 90% of patients (p<0.001). Three cases of intra-procedural single-leaflet device attachment (SLDA) occurred, and there was one case of access site bleeding requiring emergency surgery. There were no other in-hospital adverse events. Follow-up was available for 120 patients (median follow-up 182, IQR 54–356 days). TR reduction was sustained in most patients with TR ≤2+ in 83% (p<0.001). We found indications for right ventricular (RV) remodeling with a significant decrease of RV end-diastolic diameter (57±8 mm vs. 52±10 m, p<0.001). Dimensions of the inferior vena cava decreased significantly as a sign of less congestion (27±8 mm vs. 23±7 mm, p=0.004). During the follow-up period, 15 patients (10%) died, of which 7 (5%) were of a cardiovascular cause. Symptomatic improvement was significant with 66% of patients in NYHA functional class I or II at follow-up (p<0.001) and an improvement of the 6-meter walking distance (228±120 m vs. 276±121 m, p=0.001). Conclusion: Transcatheter treatment of TR with the leaflet repair system is feasible and safe. According to our data, technical success rate is high and procedural complications are rare. Patients experienced significant symptomatic improvement at follow-up with echocardiographic sustained TR reduction. Furthermore, there are indications for RV remodeling and reduced congestion. Funding Acknowledgement: Type of funding sources: None.